Cultural anthropology an applied perspective - Ferraro, Gary P. (: Thomson/Wadsworth, 2008)
Emphasizes on real world applications of the principles and practices of anthropology. This book teaches students to apply the theories, insights, and methods of cultural anthropology to those situations that they are likely to encounter in their personal and professional lives. It looks at specialized vocabularies as illustrated by chickspeak.